(untitled) - Shier, David (Boston, 2006)
Study guide with chapters corresponding directly to Hole's Essentials of Human Anatomy and Physiology, 8th edition, c2003. Provides chapter objectives, chapter overview, focus questions, mastery tests, and study activities.
Keywords: Human physiology,Human anatomy,Sinh lý người,Giải phẩu người